The relationship between child's media usage and parental influence on excessive media exposure towards children among the public attending Hospital Universiti Sains Malaysia - Rodzi, Muhammad Faris Mohd (Universiti Sains Malaysia, 2023)
Excessive media exposure can give negative impact towards children to their development this must be avoided to be happens. Parents influence and the factors of child’s media usage may be connected to the excessive media exposure towards children. The nurses must be a key role to give the health education about the negative side to the parent, therefore, raise parents' understanding and awareness of the significance of limiting their children's media exposure, which can aid in better child development in cognitive, language, social, and emotional skills. The cross-sectional study was conducted to determine the relationship between child’s media usage and parental influence on excessive media exposure towards children among public attending Hospital Universiti Sains Malysia (USM). A total 125 participants from all around areas Hospital USM who are fulfilled inclusion and exclusion criteria participated in this study. They were selected through convenience sampling method. Data collected were statistically analyzed using the Statistical Package Social Sciences (SPSS) software version of 26. This study shown smartphone were preferred devices by children to used with 82.1%. The parents in this studies showed that they were involved in their children media usage. Parent role construction, parents’ self- efficacy and parents perceived parental instruction has positive correlation between children internet use in entertainment, practical and school-or- learning related (p<0.001). The results of the present study revealed that where is a significant correlation between parenteral influence and children's media usage (p<0.001). The study finds that most of the parents not controlling the usage of their children’s media usage which because of insufficient knowledges regarding excessive media exposure negative affect to their children development.